Food insecurity among Romani adults with chronic illness in Jordan: prevalence, predictors, and public health implications - Abudari, Mohammad Othman; Razeq, Nadin Abdel; Al-Hussami, Mahmoud; Algunmeeyn, Abdullah; Abu-Abbas, Manar (Frontiers in Public Health, 2025)
BackgroundThe Roma community in Jordan, as in other parts of the world, often resides in informal settlements with limited access to employment, education, and basic services, increasing their vulnerability to food insecurity and poor health.ObjectiveThis study examined the prevalence and predictors of food insecurity among Roma adults in Jordan living with chronic diseases.MethodsA cross-sectional descriptive study was conducted among 347 Roma individuals with at least one chronic illness across four governorates. Data on demographics, health behaviors, and food security status were collected through structured questionnaire interviews. Analysis was performed using descriptive statistics and binary logistic regression to identify associated factors.ResultsFood insecurity was widespread, with 75.6% of participants reporting low food security and 14.9% very low food security. Logistic regression identified key predictors: having two or more chronic conditions increased risk (OR = 2.21, 95% CI [1.13, 4.32], p = 0.021), as did being divorced/widowed (OR = 6.56, 95% CI [1.05, 41.05], p = 0.044). Residence in Amman (OR = 0.04, 95% CI [0.01, 0.17], p < 0.001) and Madaba (OR = 0.09, 95% CI [0.02, 0.44], p = 0.003) reduced risk. Difficult healthcare access (OR = 3.50, 95% CI [1.29, 9.46], p = 0.014) elevated risk, while good/excellent self-rated health was protective (OR = 0.22, 95% CI [0.09, 0.52], p = 0.001).ConclusionFood insecurity is highly prevalent among Roma with chronic diseases in Jordan. Addressing this issue through targeted nutritional and healthcare interventions is vital to reduce disease burden and health disparities in this marginalized population.